2013
DOI: 10.1111/epi.12482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seizure‐induced syncopes:EEG,ECG, and clinical features

Abstract: SUMMARYObjective: Ictal bradycardia and ictal asystole (IA) are rare but severe complications of epileptic seizures. They are difficult to recognize within a seizure and their consequences remain unclear. Herein we aimed to extend the description of electrical and clinical features of seizures with IA and/or syncope. Methods: Among 828 patients with epilepsy who were admitted for presurgical videoelectroencephalogram (EEG) monitoring evaluation between 2003 and 2012, we selected those presenting IA and/or sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 38 publications
7
79
0
Order By: Relevance
“…14 Nguyen-Michel et al similarly reported that ictal asystole duration was longer in patients with hypoperfusion changes on EEG. 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 Nguyen-Michel et al similarly reported that ictal asystole duration was longer in patients with hypoperfusion changes on EEG. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Within the different seizure classifications, status epilepticus has the highest mortality risk, with death generally occurring within 30 days of the initial convulsant activity (39). Death often occurs in the absence of seizures and is believed to be due to an imbalance in autonomic function, resulting in altered cardiac control, electrical instability, and increased risk of lethal cardiac arrhythmias (46,51).…”
mentioning
confidence: 99%
“…One small study of seven people with ictal asystole found that none required cardiac resuscitation despite ictal asystole episodes lasting up to 25 s; only one person opted to have a permanent pacemaker; all patients were alive after 4 years of follow-up 2. However, this small cohort study does not refute the need for pacemaker insertion.…”
Section: Commentmentioning
confidence: 86%
“…Video EEG–ECG monitoring can distinguish syncope from ictal asystole. There are two distinct EEG patterns2: type 1 comprises persistent ictal discharges while type 2 comprises ictal discharges interrupted by EEG features of cerebral hypoperfusion (as in this case).…”
Section: Commentmentioning
confidence: 99%